The Measurement of The Financial Performance of Islamic Commercial Banks in Indonesia With The Maqashid Sharia Index and Comparative Performance Index Approach - Bahri, Efri Syamsul; Zam-zamiyah, Frida Tis’a; Nasution, Nursanita (IAIN Kudus, 2022)
This study aims to measure the financial performance of Islamic commercial banks in Indonesia with the Maqashid Sharia Index and Comparative Performance Index. The research design uses quantitative data using numerical data. Data were obtained from 5 Islamic commercial banks using the purposive sampling method from 2016-2019. The data analysis used the Maqashid Syariah Index and the Comparative Performance Index. This study found that Bank Rakyat Indonesia Sharia (BRIS) with the highest achievement of the Maqashid Syariah Index was 1.0881. Then, Bank Sharia Mandiri (BSM) has the lowest achievement, with a value of 0.9238. Based on the CAMEL measurement, the bank with the highest achievement was Bank Negara Indonesia Sharia (BNIS), 144.87%. At the same time, the lowest achievement was Bank Muamalat Indonesia (BMI) at 55.61%. Therefore, the merger of BSM, BNIS, and BRIS, is expected to improve the performance of the maqashid sharia index and Comparative Performance Index. Likewise, Bank Muamalat, as the first pure sharia bank, can rise and improve the performance of the sharia maqashid index and CAMEL.